METHODS FOR IMPROVING STUDENTS READING COMPREHENSION - O‘ktam qizi, Aliqulova Mohinur (PT. Antis International Publisher, 2025)
Objective: This study aims to develop and evaluate an algorithm for systematically improving students’ reading competence through integrated pedagogical, communicative, and diagnostic methods. Method: The proposed algorithm includes initial diagnostics, instructional strategies grounded in real-life scenarios, practical application in teaching practicum, and post-practicum refinement. It emphasizes the use of cognitive strategies such as summarization, self-questioning, visualization, and prediction, all of which have demonstrated significant improvements in reading comprehension. Results: The findings confirm that structured cognitive instruction fosters deeper comprehension and enhances future teachers' capacity to apply reading strategies in real-world settings. Novelty: Unlike traditional fragmented approaches, the research offers a comprehensive, stage-based algorithm grounded in dialogic education and cognitive engagement, enabling consistent skill development and practical application.